Substructures in the Isolated Galaxy Clusters - Panko, E. A.; Yemelianov, S.; Sirginava, A.; Pysarevskyi, Z.
The isolated clusters are special objects for understanding the ways of forming observed large-scale distributions of matter. One can consider the isolated clusters as objects evolving without any external influence. We present the results of the analysis of the 2D distribution of galaxies in 31 isolated galaxy clusters with redshifts z < 0.15 and the distance to the nearest neighbor less than 60h−1Mpc. We defined the morphological types of these clusters accordingly to advance Panko’s classification scheme using the “Cluster Cartography” set. The main part of these clusters belongs to the open O-type clusters without any signs of a complex structure. However, we detected the presence of the inner regular substructures for 10 clusters. They are linear substructures, X- and Y-type crosses, and compact short chains. All substructures were detected on a statistically significant level. The detected substructures have special orientations of galaxies, which note to their 3D type. Practically all studied galaxy clusters are young.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture